2022
DOI: 10.1186/s40359-022-00750-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and psychosis, depression, obsession and quality of life in Lebanese patients with schizophrenia: Any changes after 5 months of quarantine?

Abstract: Background Previous research revealed an absence of any previous studies reporting the impact that pandemics may have on psychotic symptomology, nor on the physical health of people with psychosis in response to the epidemics of the COVID-19. The direction of the impact of the COVID-19 on schizophrenia is unknown, as the risk of infection could vary from patients to patients according to clinical comorbidities, cognitive impairment, acute symptoms, and family support. To the best of our knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(44 reference statements)
0
10
0
1
Order By: Relevance
“…In relation to managing anxiety, caregivers in particular described the role of religion in coping with feelings of lack of control and assisting them in nding acceptance of the uncertainty of their circumstances. Religious faith can be a key coping strategy for people with mental health conditions and families in South Africa [74] and some other LMIC [75,76]. Its function of being a route to nd meaning and hope, as well as a source of support and social connection, can be a key aspect of recovery [11,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to managing anxiety, caregivers in particular described the role of religion in coping with feelings of lack of control and assisting them in nding acceptance of the uncertainty of their circumstances. Religious faith can be a key coping strategy for people with mental health conditions and families in South Africa [74] and some other LMIC [75,76]. Its function of being a route to nd meaning and hope, as well as a source of support and social connection, can be a key aspect of recovery [11,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Der Großteil der Studien beschreibt negative Auswirkungen der COVID-19-Pandemie auf das Leben von Menschen mit Schizophrenie [9][10][11][12][13][14][15][16][17]. Andere Studien konnten bei unterschiedlichen untersuchten Faktoren keine Verschlechterung feststellen [18][19][20][21].…”
Section: Was Ist Bereits Bekannt?unclassified
“…Blockchain technology is used by public and commercial (hired) agencies to address the problems of plagiarism and other forms of fake material on these sites. The European Centre for Disease Prevention and Control estimates that 10 million people are affected with this virus every year [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], making prevention efforts difficult due to a lack of available tools like immunizations and a COVID-19 protection package [21][22][23][24][25][26][27][28][29][30]. Numerous studies demonstrated that X-rays are crucial in the initial phases of diagnosis of the virus.…”
Section: Introductionmentioning
confidence: 99%